THE LECTURER AND THE STUDENTS’ PERCEPTION OF THE IMPLEMENTATION OF HYBRID LEARNING IN ENGLISH TEACHING - Ilyas, Nurqalbhi; Munir, Munir; Muliati, A. (Universitas Negeri Makassar, 2023)
This research aims to determine the perceptions of lecturers and students regarding the application of hybrid learning methods in teaching English. This research uses qualitative methods to achieve research objectives. Participants in this research were 1 lecturer and 5 students from the English Education Department, Faculty of Language and Literature, Makassar State University. Participants were selected using random techniques. The instruments of this research are interviews and documentation. The results of this research are, 1) lecturers have a positive perception of hybrid learning so that it can be an alternative in learning amidst Covid-19; 2) students have a positive perception of hybrid learning which makes it easier for students to understand the learning provided by the lecturer. In terms of benefits, lecturers and students feel that implementing the hybrid learning method is very effective and is one solution for smooth learning.